Balance in seniors who exercise, considering different levels of fear of falling Equilíbrio em idosos praticantes de atividade física com diferentes níveis de medo de cair - Hauser E.* (2017)
© 2017, Eduem - Editora da Universidade Estadual de Maringa. All rights reserved.The aging process brings changes to one’s body balance and may trigger a fear of falling. The aim of this study was to compare and verify correlation between different methods that assess body balance among elderly individuals who exercise, according to different levels of fear of falling. The sample was composed of 186 individuals (68.28±6.years) who exercise. Balance assessment used Timed Up and Go, Unipedal Stance, Sitting-Rising and Functional Reach tests. A question about fear of falling was applied in the form of an interview. Statistical analysis used Spearman and Kruskall Wallis correlation. In results, Timed Up and Go (7.13±1.6s), Unipedal Stance (20.52±9.9s), Sitting-Rising (12.43s±3.2s) and Functional Reach (29.51±6.5) showed significant correlation with fear of falling. Individuals less afraid of falling showed better balance performance when compared to those not afraid of falling. In conclusion, better balance performance can contribute to decreasing fear of falling.